2001
DOI: 10.1149/1.1378289
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Power Density of LSGM-Based Solid Oxide Fuel Cells Using New Anode Materials

Abstract: Chemical reactions between the superior perovskite oxide-ion conductor Sr- and Mg-doped LaGaO3 (LSGM), CeO2, and NiO have been studied by powder X-ray diffraction. The results showed that an extensive reactivity occurs as a result of La migration driven by a gradient of La chemical activity. La migration across the LSGM/electrode interfaces in a fuel cell leads to the formation of resistive phases at the interface, either LaSrGa3O7 or LaSrGaO4. Use of 40 mol % La2O3 -doped CeO2 as an interlayer betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(132 citation statements)
references
References 34 publications
4
123
5
Order By: Relevance
“…The perovskite ionic conductor La 0.8 Sr 0.2 Ga 0.87 Mg 0.13 O 3 (LSGM) has been shown to be an excellent electrolyte candidate for SOFCs operating at intermediate temperatures. [6][7][8] Besides the electrolyte material, it has also been shown that the cathode material becomes the major obstacle in achieving high cell performance when lowering the cell operating temperature. 9 Generally speaking, the oxygen reduction process at the cathode is mainly responsible for the polarization loss of the fuel cell at intermediate temperatures.…”
mentioning
confidence: 99%
“…The perovskite ionic conductor La 0.8 Sr 0.2 Ga 0.87 Mg 0.13 O 3 (LSGM) has been shown to be an excellent electrolyte candidate for SOFCs operating at intermediate temperatures. [6][7][8] Besides the electrolyte material, it has also been shown that the cathode material becomes the major obstacle in achieving high cell performance when lowering the cell operating temperature. 9 Generally speaking, the oxygen reduction process at the cathode is mainly responsible for the polarization loss of the fuel cell at intermediate temperatures.…”
mentioning
confidence: 99%
“…There were LaSrGaO 4 and LaSrGa 3 O 7 precipitates detected when the composite cathode SSC-SDC/LSGMC was calcined on LSGM. La diffusion into CeO 2 -based materials is strongly suspected in this case due to previous research (28). Possible La diffusion into SSC-SDC powder could stem from LSGMC powder or LSGM pellet and could lead to a La deficiency in the LSGM phase.…”
Section: Resultsmentioning
confidence: 75%
“…Indeed, La diffused from LSGM into GDC during firing and the loss of La from LSGM likely contributes to de-stabilization of the perovskite phase, which exists over a relatively narrow composition range. Note that La loss occurs because GDC does not provide the high-La activity of LDC, which is sometimes used as a protective barrier layer with LSGM to avoid La loss and reactions with anode materials [15][16][17]. The present case where GDC, LSCrRu, and pores were in contact with the LSGM is also different than prior work where LDC was a continuous layer separating the LSGM and anode.…”
Section: Discussionmentioning
confidence: 82%